PREDIKSI KERENTANAN EROSI DAN SEDIMENTASI DAS SEMARANG TIMUR - Risdiana Cholifatul Afifah; Fitria Maya Lestari; Son Haji (Fakultas Teknik dan Ilmu Komputer (FASTIKOM) UNSIQ, 2023)
The East Semarang watershed is an area with diverse land conditions and the majority of the upstream and downstream areas are converted into settlements. This results in an increase in the rate of erosion which erodes the land and causes sedimentation in the downstream watershed. The higher the erosion rate, the higher the sedimentation, therefore the prediction of the erosion value is important as an indicator to recommend natural resource conservation activities. The purpose of this study is to predict erosion and sedimentation rates, and to recommend good conservation methods in an effort to reduce soil erosion. Land erosion analysis was obtained from the overlay of erosion parameter layers with the help of the ArcGIS program using the USLE (Universal Soil Loss Equation) method. Not all of the eroded soil surface in the watershed will be transported to the river, but some will settle on the watershed surface due to the interaction between the flow and the watershed surface. Sediments carried by measured river flows at the outlet were analyzed using the SDR (Sediment Delivery Ratio) method. Then it can be known the amount of sediment per year in the East Semarang watershed or by the term SY (Sediment Yield). Based on the calculation of land erosion in the East Semarang watershed, as big as 816,910.81 tons/year, which resulted in a total sedimentation of 4,641.39 tons/year. Erosion hazard classifications vary from very light to very severe, with the majority of the class being very severe in the upstream region with an area of ​​7,003.55 Ha. The recommendation proposed to overcome or reduce erosion is technical conservation, namely terracing and check dam techniques.